Genetic testing for thrombophilia in case of unprovoked episode of pulmonary embolism - Kirieieva, T.V.; Pertseva, T.A.; Kravchenko, N.K.; Basina, B.O. (Medicni Perspektivi, 2021)
Venous thromboembolism (pulmonary embolism (PE) and deep vein thrombosis (DVT)) is the third among all cardiovascular syndromes in the world, second only to heart attack and stroke. Estimation of clinical probability of this condition takes into account many factors, including age. But in case of PE probability in young patient data of scales such as Geneva Score (Revised), Wells' criteria for pulmonary embolism, the PERC rule may be misleading. For this group a new influential factor emerges – thrombophilia. The aim of our work was to demonstrate the approach to identifying whom and when to test for genetic predisposition for thrombosis, based on a clinical case of young male with unprovoked episode of PE. Testing patients for thrombophilia is a good way to develop a personalised approach in case of prescribing long-term anticoagulant treatment. Moreover, patient’s awareness about congenital condition helps to increase complience which is crucial, due to the fact that in case of unprovoked pulmonary embolism another episode can occur in up to 50 % of cases during the next 5 years. In addition, further accumulation and analysis of data on the amount of genetic risk factors for thrombosis will expand our understanding of this issue and in the future will allow us to better diagnose and treat this condition.